DIGITALISASI PELAYANAN PUBLIK MELALUI PEMBANGUNAN PORTAL SISTEM INFORMASI DESA SERDANG, KECAMATAN MERANTI, KABUPATEN ASAHAN - Diva Agustin Purba; Nazma Aulia; Maulidia Manurung; Adinda Nasution; Khairul Shaleh (Smart Education, 2026)
Public services at the village level are still largely delivered conventionally, causing limitations in service speed, information transparency, and data updating. This Community Service (KKN) activity aims to digitize public services in Serdang Village, Meranti Sub-district, Asahan Regency, by developing a web-based Village Information Portal accessible at desa-serdang.my.id. The portal was built using the open-source OpenSID platform, which was customized and populated with village data to fit local needs. The implementation followed common development stages: requirements analysis through observation and interviews, installation and configuration on hosting and a domain, interface customization and content entry, module activation, testing, and training for officials. The portal provides village profiles and officials, a GIS-based map, a photo gallery, news, transparency documents such as the village budget (APBDes) and LPPD, population statistics, an MSME catalog and citizen service board, and a Citizen Self-Service feature for online letter requests, social-aid verification, and complaints. Black-box testing showed all features worked as intended. The portal eases public access to information and services, strengthens governance transparency, and opens space to promote the local economy, becoming an initial step in the digital transformation of Serdang Village toward a smart village.